Faktor-Faktor yang Mempengaruhi Minat Masyarakat Terhadap Investasi Emas di Pegadaian Syariah - Yusuf, Yuslaidar; Agustina, Maya; Husni, Almira Sabrina; Fitri, Aida (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
Indonesia’s economic growth is inextricably linked to the development of both the financial and real sectors. Investment is fundamentally defined as the postponement of current consumption to achieve potential future benefits, a process inherently accompanied by uncertainty and risk. As a result, this delay necessitates adequate compensation, commonly referred to as investment returns or gains. The purpose of this study was to analyze the influence of factors that influence Public Interest in Gold Investment at Pegadaian Syariah. The risk factors that are the objects of research include Interest, Promotion, Service Quality. The population in this study is the people of Banda Aceh City, this type of research uses a quantitative method, the population in this study is the entire community in Banda Aceh, the sample collection technique in this study is by direct observation of the questionnaire using multiple linear regression analysis, Based on the results of the analysis and conclusions that have been put forward, that there is a positive relationship between promotion, service quality and public interest. This proves that promotion and service quality are one of the factors that can determine public interest in investing in gold at Pegadaian Syariah.